The Role of Religious Moderation in Enhancing Social Harmony and Interfaith Tolerance among University Students - Yosefo Gule; Johannes Keliat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Radicalism and intolerance among religious communities in universities indicate a lack of understanding of religious moderation among students. This study aims to analyze the role of religious moderation in strengthening social harmony and interfaith tolerance among students of different faiths. The methodology used is a literature review, with data from journals, books, and relevant research conducted over the past five years. The results reveal a significant gap between the concept of religious moderation and its actual practice among students in campus life. While moderation is emphasized in educational policies, it has not yet been fully internalized as a social behavior, particularly in students' everyday interactions. These results suggest that religious education based on moderation should focus on transforming theoretical concepts into tangible actions, not merely discourse. The study also identifies that moderate religious values, such as balance, justice, and tolerance, are crucial for reducing intolerance and radicalism. Therefore, the study recommends strengthening campus policies and increasing student participation as key agents of interfaith harmony. Additionally, it suggests future research using qualitative field approaches to explore how religious moderation is applied in students' daily lives.